Evaluation of International Competitiveness - Ramanauskas, Gediminas (Ekonomika, 2004)
Competitiveness can be defined in a number of ways. We can think of it as of a successful performance of a company or organization; or we may talk about competitiveness in a macro context such as a favourable exchange rate of a national currency. Can we also talk about competitiveness of a nation? What is it and how can it be evaluated?There does not seem to be a common definition of what the international competitiveness of nations is. Some feel that the very notion of international competitiveness of nations is unfair and unacceptable. They argue that the nations themselves do not compete, their enterprises do. For others the notion of international competitiveness of nations is fair. They believe that creating appropriate measures of international competitiveness is central for tracking and understanding the sources of competitiveness of countries.In this paper I classify and compare the measures developed by various authors. I suggest that the studies on the measurement of competitiveness can be classified into five groups:1. Particular sector studies.2. Competitiveness studies at the regional / country level.3. Particular competitiveness indicator studies.4. Competitiveness studies at an international level.5. Cross-country economic policy studies.Since the competitiveness studies serve a different audience and purpose, we cannot discuss which is best without first asking: best at what?